Experiences of members of the care triad on transitioning from home to a nursing home: a qualitative study - Skudlik, Stefanie; Lüftl, Katharina; Thalhammer, Regina; Zaglacher, Melina; Müller, Martin (BMC geriatrics, 2025)
The transition from home to a nursing home is an emotionally and organisationally challenging process for the care triad, consisting of older adults in need of care, their informal caregivers, and health professionals. Although this transition is known to occur in three phases, no study has comprehensively examined the experiences of care triad members across all phases, and evidence-based interventions to support informal caregivers and older adults through this highly stressful process are lacking. This study aimed to explore the experiences of care triad members, with a focus on identifying problems, strategies, required support, and suggestions for improvement across all three transition phases. These insights will serve as a basis for developing an intervention to enhance the transition.
Gesehen am 30.01.2026